Palaeoenvironment and basin architecture of the Lower Jurassic Ab-Haji Formation, east-central Iran - Salehi, Mohammad Ali (2014)
Fil: Fil: Salehi, Mohammad Ali. Department of Geology, Faculty of Science, Ferdowsi University of Mashhad, Iran.